Cultural Factors Influencing Socio-Economic Development of Batwa Community in Kisoro Municipality. - Niyigaba, Brendah (Kabale University, 2024)
The study assessed cultural factors influencing the socio-economic development of the Batwa community in Kisoro municipality. The objectives of the study were to assess the impact of cultural norms and values on Batwa education in Kisoro municipality, to find out the challenges faced by Batwa children towards achieving education in Kisoro municipality, to suggest possible interventions to reduce the challenges faced by Batwa children towards achieving education in Kisoro municipality. The study adopted a descriptive research design. Data collection tools were both questionnaires and interview guides. Results of the study revealed that that Batwa are hindered by their cultural norms and values towards achieving their education. The study concluded that cultural factors influencing the socio-economic development of the Batwa community in Kisoro Municipality provide a comprehensive analysis of how cultural norms and practices impact various aspects of life within this community. The findings highlight the complex interplay between traditional cultural factors and socio-economic development, revealing both challenges and opportunities for progress. The study recommended that the Ministry of Education should develop scholarship programs and financial aid to reduce economic barriers to education and government should establish community schools that incorporate Batwa cultural practices and are accessible within the community.